Design for Maintainability and Availability Analysis for System Design - Maurya J.; Bharti O.P.; Anand Kumar K.S.; Saket R.K. (My University, 2025)
Engineered systems typically undergo maintenance to ensure their continued operation. This maintenance encompasses repairing malfunctions and conducting upkeep tasks. The ease with which repairs and maintenance tasks can be executed defines the system’s maintainability. Maintained systems may undergo two types of maintenance: corrective maintenance (CM) and preventive maintenance (PM). Corrective maintenance involves actions taken to restore a system from a failed state to a functional one. Active maintenance time involves various activities such as reviewing repair instructions before starting the actual repair process and verifying the repair’s effectiveness. It may also involve documenting the repair if necessary before the specified equipment can be considered ready for corrective maintenance activities, such as in the case of aircraft (referred to as mean active corrective maintenance time or MACMT). In this chapter, systems maintainability and availability have been elaborated with different methodologies, where PM aims to prevent failures from occurring in the first place and includes activities like servicing, reliability improvements, cleaning, lubrication, and inspections to detect issues like cracks, and calibration. The effectiveness of PM tasks is often measured by the time required to complete them at their specified intervals. © 2024 by The Institute of Electrical and Electronics Engineers, Inc. All right reserved.